Phytochemical Composition and Antioxidant Potential of Oven Heated and Microwave Treated Ginger (Zingiber officinale Roscoe) - Nawaz, Haq; Shad, Muhammad Aslam; Aziz, Aziz ur Rehman; Muntaha, Sidra Tul; Muzaffar, Saima (Free Radicals and Antioxidants)
Objective: The study was designed to investigate the effect of heating in the simple oven and microwave treatment on phytochemical composition and antioxidant potential of ginger (Zingiber officinale R.), a popular food ingredient of medicinal importance. Methods: Dried ginger was ground to fine powder and subjected to heating in the simple oven and microwave oven in an increasing order of heating time (5, 10, 15, 20 and 25 min). The heat-treated samples were extracted in methanol and analyzed for their phytochemical composition and antioxidant potential. Results: A time-dependent significant (p<0.05) negative effect of both treatment methods was observed on total phenolic acids (TPA), total tannins content (TTC), total flavonoids content (TFC), total antioxidant activity (TAOA), 2, 2-diphenyl-1-picrylhydrazyl radical scavenging capacity (DPPH RSC) and hydroxyl radical scavenging capacity (HRSC). Both treatments methods showed the significant positive effect on β-carotene bleaching capacity (BCBC), reducing power (RP) and iron chelating activity (ICA). TPA and TAOA of oven heated, TTC and RP of microwave-treated and TFC, BCBC, and HRSC of ginger varied exponentially while TTC and RP of the oven heated, TPA and TAOA of microwave-treated and ICA and DPPH RSC showed linear variation in response to treatment time. Conclusion: Both heating methods have a significant time-dependent effect on the phytochemical composition and antioxidant activity of ginger. This study provides useful information to the manufacturers and consumers regarding the potential benefits of ginger and effect of various heat treatments methods on its medicinal value.
Keywords: Antioxidant activity; β-carotene bleaching assay; Free radical scavenging capacity; Ginger (Zingiber officinale); Microwave treatment